BORROWER'S LIABILITY FOR DAMAGED MOTORCYCLE AFTER RETURN - Yunda Ameilia; Nurhilmiyah; Masitah Pohan (International Journal of Cultural and Social Science, 2026)
Motorcycle loan agreements that are made verbally often cause legal problems, especially when the motorcycle is damaged after being returned to the owner. This study aims to find out the legal provisions that govern motorcycle loan agreements and the liability of the borrower for the damage that occurs. The research method used is normative legal research with a legislative approach and a case approach, which is analyzed qualitatively based on primary and secondary legal materials. The results of the study show that the loan agreement is regulated in Articles 1740 to 1753 of the Civil Code, and the borrower is responsible for the damage to the motorcycle caused by its negligence in the form of compensation as a result of default.